Water and Land Productivity of Lettuce (Lactuca sativa) at Floating Pot on Wetland - Lily Endah Diansari (Sriwijaya Journal of Environment, 2019)
The objective of this study was to determine the values of water productivity and land productivity at the floating pot on wetland and to find out whether the floating pots were optimal or not for agriculture in wetlands. The planting media used were mineral soil, and peat soil consisting of 0%, 30%, 50%, 70% and 100% each of which had hydraulic conductivity values respectively except the 100% was 36.07 cm/hour, 38.33 cm/hour, 51.23 cm/hour and 69.60 cm/hour. The water delivery used was legacy cloth which had hydraulic conductivity value was 158.4 cm/hour. The floating pots were applied to the experiment tank in the greenhouse. The decrease in water level in the experimental pool was total evapotranspiration for all plants in five types of planting media. Water level reduction during the 41-days planting period was 40.56 mm with a total water volume was 0.081 m3. The productivity values of land and water in the 0%, 30%, 50%, 70% and 100% peat planting media, respectively were 1.29, 1.25, 1.06, 0.8 dan 0 kg/m2 dan 1.63, 1.63, 1.38, 1.04 dan 0 kg/m3.The objective of this study was to determine the values of water productivity and land productivity at the floating pot on wetland and to find out whether the floating pots were optimal or not for agriculture in wetlands. The planting media used were mineral soil, and peat soil consisting of 0%, 30%, 50%, 70% and 100% each of which had hydraulic conductivity values respectively except the 100% was 36.07 cm/hour, 38.33 cm/hour, 51.23 cm/hour and 69.60 cm/hour. The water delivery used was legacy cloth which had hydraulic conductivity value was 158.4 cm/hour. The floating pots were applied to the experiment tank in the greenhouse. The decrease in water level in the experimental pool was total evapotranspiration for all plants in five types of planting media. Water level reduction during the 41-days planting period was 40.56 mm with a total water volume was 0.081 m3. The productivity values of land and water in the 0%, 30%, 50%, 70% and 100% peat planting media, respectively were 1.29, 1.25, 1.06, 0.8 dan 0 kg/m2 dan 1.63, 1.63, 1.38, 1.04 dan 0 kg/m3.